1999
DOI: 10.1159/000023469
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Cardiovascular Effects of High-Dose Growth Hormone Treatment in Growth Hormone-Deficient Children

Abstract: Aim: To investigate the possible cardiac morphofunctional alterations inducd by prolonged and high-dose GH therapy in a group of 14 children with isolated GH deficiency. Patients and Methods: Patients were evaluated at phase 1, after 1.1 ± 0.6 years of treatment with GH 0.93 ± 0.13 U/kg/week, and at phase 2, after 5.5 ± 2.1 years of therapy 0.89 ± 0.11 U/kg/week. At each phase left ventricular volume, mass and systolic function were evaluated by two-dimensional guided M-mode echocardiography; left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…The results of the present study are different from those obtained in our recent survey where the cardiac morphology and function were investigated, with the same modalities, in a group of GHD children treated with the same dosage of GH (1 U/kg/ week) and for a comparable period of time [6]. In that study we showed that the patients had an increase in mass and mass/volume ratio, reduced systolic performance and initial alterations of the diastolic function of the left ventricle after long-term therapy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are different from those obtained in our recent survey where the cardiac morphology and function were investigated, with the same modalities, in a group of GHD children treated with the same dosage of GH (1 U/kg/ week) and for a comparable period of time [6]. In that study we showed that the patients had an increase in mass and mass/volume ratio, reduced systolic performance and initial alterations of the diastolic function of the left ventricle after long-term therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Left ventricular (LV) hypertrophy, together with increased morbidity and mortality from cardiovascular diseases, are well-known complications of GH excess in acromegalic patients [4, 5]. Furthermore, we also found that GHD children treated for many years with high doses of GH show subclinical morphofunctional alterations of the left ventricle [6]. Since previous studies in TS patients were more focused on the effects of GH treatment on cardiac morphology [7, 8, 9], we decided to further explore this field by evaluating heart function, as well as morphology, in TS patients treated with high-dose GH for a mean period of 4.9 years.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find, however, any signs of glucose intolerance in our patients. Moreover, the potential side-effects of highdose GH treatment on the cardiovascular system have not as yet been fully clarified (19). The theoretical risk of an increased incidence of adulthood cancer associated with an elevated serum insulin-like growth factor (IGF)-I level in a GH recipient, is, however, lowered by the fact that GH also increases the level of IGF-binding protein-3, which would inhibit IGF-I action (20).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of normal volunteers with GH doses similar to those used in TS (0.06 mg/kg/d) increased cardiac output and left ventricular mass in just 4 weeks (16). Finally, treatment of GH-deficient children with exogenous GH has been associated with disproportionate left ventricular growth (17,18). Given the cardiac involvement in TS there has been concern over potential adverse cardiovascular effects of GH treatment.…”
mentioning
confidence: 99%
“…Thus we confirm the earlier studies that lacked control groups with TS, and extended our own previous study showing no apparent effect of GH on aortic diameter in TS (26). It is curious that there seems to be no cardio-selective effect by GH in girls with TS, although GH treatment of GH-deficient children has been associated with disproportionate left ventricular growth (17,18). Perhaps this is because in GH deficiency there is a relative cardiac hypoplasia and associated catch-up growth with GH treatment.…”
mentioning
confidence: 99%